THE INFLUENCE OF CASH FLOW ON A COMPANY’S PROFITABILITY LISTED ON THE STOCK EXCHANGE OF THAILAND DURING THE COVID-19 - Vattanajirapun, Thunyaphat; Pimsawat, Jongjit; Maleehuan, Supawan (Journal of Social Science and Cultural, 2023)
This research aimed to study the influence of cash flow on a company’s profitability listed on the Stock Exchange of Thailand during the COVID-19 situation. The secondary data were collected from 157 companies on a yearly basis from 2020 to 2022 by the Panel Data method, comparing to the Fixed Effect Regression Model (FEM) compare with Random Effect Regression Model (REM). The results showed that the appropriate method of estimating the coefficient was to apply the fixed-effect Panel OLS method and the stockholder return rate model. The listed companies on the Stock Exchange of Thailand were suitable (Prob. = 0.0000). The net cash from financing activities (In_CFFi,t) and the number of board of directors influenced the stockholder return rate in the Stock Exchange of Thailand in opposite directions with a statistically significant at 1% and 5% respectively and the R - squared value was 0.7153. When considering the return on capital asset pricing model, the listed companies on the Stock Exchange of Thailand were suitable (Prob. = 0.0000). The net cash from financing activities (ln_CFFi,t) and the number of board of directors influenced the stockholder return rate in the Stock Exchange of Thailand in opposite directions with a statistically significant at 1% and 10% respectively and the R - squared value was 0.7558. Finally, when the net profit margin model was applied with the listed companies on the Stock Exchange of Thailand, it was appropriate (Prob. = 0.0000). The net cash from financing activities (ln_CFFi,t) and the number of board of Directors influenced the net profit margin on the Stock Exchange of Thailand. in opposite directions with a statistically significant at 1% and 5%, respectively and the R - squared value was 0.7558.